Examination of Physical Activity and Quality of Life of University Students in the COVID-19 Pandemic Period - Kıvrak, Ali Osman (Progress in Nutrition, 2021)
Study Objectives: With this study, it was aimed to examine the physical activity and quality of life of university students during the COVID-19 pandemic period. Methods: A total of 495 university students, 192 female, and 303 males, participated in the study. While the personal information form created by the researcher was used for socio-demographic data, the short form of the "International Physical Activity Questionnaire" was used to determine the physical activity level, and the "SF-36" scale was used to determine the quality of life. The homogeneity and variances of the data were tested, the independent samples t test was used for pairwise comparisons, the One-Way ANOVA was used for multiple comparisons, and the Tukey HSD test was used to determine the source of difference. Results: While no statistical change was observed in the quality-of-life dimensions depending on the gender factor, it was determined that the value for females was statistically higher than the value for males in physical activity walking and total MET values (p